2015
DOI: 10.1371/journal.pone.0127090
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative/Nitrative Stress and Inflammation Drive Progression of Doxorubicin-Induced Renal Fibrosis in Rats as Revealed by Comparing a Normal and a Fibrosis-Resistant Rat Strain

Abstract: Chronic renal fibrosis is the final common pathway of end stage renal disease caused by glomerular or tubular pathologies. Genetic background has a strong influence on the progression of chronic renal fibrosis. We recently found that Rowett black hooded rats were resistant to renal fibrosis. We aimed to investigate the role of sustained inflammation and oxidative/nitrative stress in renal fibrosis progression using this new model. Our previous data suggested the involvement of podocytes, thus we investigated r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 62 publications
2
24
0
Order By: Relevance
“…Nephrin has important effects in controlling the integrity and functions of the podocyte slit diaphragm structure ( 16 ). In a previous study, ADX induced direct toxic damage to the podocytes and loss of nephrin in urine ( 13 ). Immunohistochemical staining revealed that the numbers of nephrin-positive cells were dramatically decreased in the glomeruli of ADX-injected mice and were significantly restored by LJ1888 treatment.…”
Section: Resultsmentioning
confidence: 87%
See 2 more Smart Citations
“…Nephrin has important effects in controlling the integrity and functions of the podocyte slit diaphragm structure ( 16 ). In a previous study, ADX induced direct toxic damage to the podocytes and loss of nephrin in urine ( 13 ). Immunohistochemical staining revealed that the numbers of nephrin-positive cells were dramatically decreased in the glomeruli of ADX-injected mice and were significantly restored by LJ1888 treatment.…”
Section: Resultsmentioning
confidence: 87%
“…ADX leads to direct toxic injury of the glomerular filtration barrier including podocytes, the glomerular basement membrane and glomerular endothelial cells. Podocyte damage induces loss of protein and nephrin in the urine ( 13 ). In order to investigate the effects of LJ1888 on podocyte injury in ADX-induced nephropathy, we checked the urinary excretion of protein and albumin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DOXO treatment may also result in an inflammatory response following penetration of the epithelial barrier by bacterial products, or via another distinct pathway, such as the AKT-dependent inflammation that leads to cardiomyopathy following DOXO, or the CCL2-dependent inflammation that leads to renal fibrosis following DOXO. 32,33 To elucidate these mechanisms, future investigations will evaluate epithelial permeability, as well as the role of the inflammatory response, following DOXO. We hypothesize that treatment with DOXO causes an increase in the permeability of the epithelial barrier (due to a transient induction of increased apoptosis), concomitant with increased association of enteric bacteria with the mucosa, allowing bacterial products to penetrate and induce an inflammatory response, resulting in the significant mucosal damage (and repair) observed in our studies.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, resveratrol rescued HDF-induced inflammatory response and oxidative stress which will strongly induce renal fibrosis. [42][43][44] These results demonstrated that resveratrol can play beneficial roles both in vivo and in vitro.…”
Section: Hfd and Hg Culture Comparisonmentioning
confidence: 99%